Before it is over: A family's experience with end-of-life care during COVID-related restrictive visitation policies - Andjela Kaur (The Beryl Institute, 2022)
It is not uncommon in the American medical community that a personal narrative sparks a conversation about a controversial topic. In 1988 the Journal of American Medical Association published a narrative by a medical doctor which provoked a debate on euthanasia within the readership of the journal and the greater public. The testimony that I am presenting aims to invite a public dialogue on the harmful effects of restrictive visitation policies brought on by the COVID -19 pandemic. The story of my family's experience during the end-of-life care for my mother, a COVID patient, illustrates how urgent is the need to rethink the restrictive visitation policies so as to protect patients from unnecessary suffering. In order to battle pandemic-related stress and fatigue medical staff and families must work together to improve patient care. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.